MiRNA Profiling in Pectoral Muscle Throughout Pre- to Post-Natal Stages of Chicken Development - Chen, Min; Zhang, Shaolan; Xu, Zhongxian; Gao, Jian; Mishra, Shailendra Kumar; Zhu, Qing; Zhao, Xiaoling; Wang, Yan; Yin, Huadong; Fan, Xiaolan; Zeng, Bo; Yang, Mingyao; et al. (Frontiers in Genetics, 2020)
MicroRNA (miRNA) is known to be an important regulator of muscle growth and development. The regulation of microRNA on the skeletal muscle phenotype of animals is mainly achieved by regulating the proliferation and differentiation of myoblasts. In this study, we sequenced a total of 60 samples from 15 developing stages of the pectoral muscle and 5 other tissues at 300 days of Tibetan chicken. We characterized the expression patterns of miRNAs across muscle developmental stages, and found that the chicken growth and development stage was divided into pre-embryo, late embryo and growth period after birth. We identified 81 and 21 DE-miRNAs by comparing the miRNA profiles of pectoral muscle of 3 broad periods and different tissues, respectively; and 271 miRNAs showed time-course patterns. Their potential targets were predicted and used for functional enrichment to understand their regulatory functions. Significantly, GgmiRNA-454 is a time-dependent and muscle-specific miRNA. In order to elucidate the role of gga-miRNA-454 in the